Oxidation behavior of a cathodic arc evaporated Cr0.69Ta0.20B0.11N coating - Kainz, Christina; Letofsky-Papst, Ilse; Saringer, Christian; Krüger, Hannes; Stark, Andreas; Schell, Norbert; Pohler, Markus; Czettl, Christoph (Journal of vacuum science & technology / A (JVST), 2023)
CrTaBN hard coatings deposited by cathodic arc evaporation are a promising new material class for use in demanding applications, due to their high hardness and good thermal stability in protective atmosphere. Up to now however, studies on the detailed oxidation mechanism of quaternary CrTaBN coatings are lacking in the literature. Thus, within this work, the oxidation behavior of a Cr0.69Ta0.20B0.11N coating grown by cathodic arc evaporation was studied in a combinatorial approach of advanced characterization techniques. In situ high-energy x-ray diffraction at a synchrotron radiation facility showed that up to ∼1100 °C, only the face-centered cubic (fcc) CrxTayB1-x-yN solid solution of powdered CrTaBN contributes to the crystalline phase composition. As the temperature is further increased, tetragonal CrTaO4 and rhombohedral Cr2O3 form. In situ high-temperature Raman spectroscopy evidenced that B2O3 contributes to the phase composition of the material in the temperature regime from ∼600 to 1000 °C. Applying high-resolution transmission electron microscopy allowed to identify the presence of four discrete zones in a partly oxidized CrTaBN coating on sapphire: intact fcc-CrTaBN at the interface to the substrate, followed by a Cr-deficient and Cr-enriched layer, respectively, and a porous layer with small grains at the surface.
Publisher Copyright: © 2023 Author(s).